Information Technologies in the Tax Administration System of VAT - SOLEHZODA, Ayubjon (Journal of Advanced Research in Law and Economics; Vol 8 No 4(26) (2017): JARLE Volume 8 Issue 4(26) Summer 2017, 2017)
The article considers topical issues of electronic tax administration value added tax of the Republic of Tajikistan. Prospects for the use of information technologies in tax administration are investigated. Elements and the potential of using new forms of interaction and information technology, the Internet, and electronic information exchange in taxation and VAT administration are identified and articulated. The author indicates the necessity of the development of electronic tax administration of VAT with the development of information technology. The ways of improvement of these forms and methods are suggested.